Computer-aided molecular design of CO2-based mixture working fluid harvesting engine waste heat. (5th June 2023) - Wang, Jingyu; Tian, Hua; Sun, Rui; Wang, Xuan; Li, Ligeng; Zhang, Xuanang; Shu, Gequn
Highlights: A design method for the CO2 -based mixture working fluid harvesting waste heat. Concise molecular constraints are developed to identify molecules. Promotion of 16.33% and 17.60% in system efficiency and net power can be achieved. Short-chain additives are better in CO2 -based mixture transcritical power cycle. Abstract: The CO2 transcritical power cycle is an important method for recovering waste heat. The cycle performance can be further improved by using CO2 -based mixtures instead of pure CO2 . To avoid the empirical screening of CO2 mixtures, a computer-aided molecular design method, which is based on the group contribution method and perturbed chain-statistical associating fluid theory equations of state, is used for the first time in this study to design CO2 -based mixtures for power cycles. The calculation method for group to system thermodynamic performance is established and verified. A molecular identification model is used to obtain all compounds based on the group library, calculate their thermodynamic properties for ranking, and find the best CO2 -based mixture in the global range. The performance and cost of the expander are also briefly discussed. Taking the simple transcritical power cycle as an example, the results show that when the mole fraction of CO2 is greater than 0.70, the optimal CO2 -based mixture, CH3 -C≡CH, can increase the system efficiency and net output work by 16.58% (9.07%) and 17.88% (17.87 kW), respectively, compared to those of pure CO2 . The peak system efficiency is 9.83% at an evaporation pressure of 24 MPa. Shorter-chain additives can improve thermodynamic performance, which is demonstrated by extracting the contribution of each group to the performance of the system using statistical methods. This method enables the ranking of CO2 mixtures on a global scale and provides some rules. It is also suggested that further economic analysis is necessary.